An appraisal of a systems procedure with particular reference to a tyre manufacturing organisation: 2nd year ergonomics course - Beevis, D.; Leamon, T. B.; Lovesey, E. J.; Neale, J. G.; Strank, R. H. D. (College of Aeronautics)
The objective of this project was to show how the procedures and techniques of system design may be used to evolve a soft system. In this project a systems design procedure was applied to a tyre ordering and despatch method for a large manufacturing organisation.